Potential for tourism in the demographically threatened region of Jurklošter - Topole, Maja (Acta geographica Slovenica, 2009)
This article examines the demographically threatened region of the local community of Jurklošter in the southeastern part of the Alpine Sava Hills (Posavsko hribovje), part of the municipality of Laško. It draws attention to the natural and social conditions in the region after the Second World War, which led to the steady depopulation of the area. The paper presents the characteristics of the geographical location, settlement, settlements, population and land use, and economic development. It emphasizes the significance of the exceptional natural and cultural heritage as bases for strengthening the role of tourism and recreation, which along with some complementary activities could help reverse negative population trends and provide new sources of income. It deals primarily with natural and cultural motives as important components of the tourism potential of the region.